Functionalized Electrospun Nanofibers as Colorimetric Sensory Probe for Mercury Detection: A Review - Brabu Balusamy; Anitha Senthamizhan; Tamer Uyar (Sensors, 2019)
Mercury is considered the most hazardous pollutant of aquatic resources; it exerts numerous adverse effects on environmental and human health. To date, significant progress has been made in employing a variety of nanomaterials for the colorimetric detection of mercury ions. Electrospun nanofibers exhibit several beneficial features, including a large surface area, porous nature, and easy functionalization; thus, providing several opportunities to encapsulate a variety of functional materials for sensing applications with enhanced sensitivity and selectivity, and a fast response. In this review, several examples of electrospun nanofiber-based sensing platforms devised by utilizing the two foremost approaches, namely, direct incorporation and surface decoration envisioned for detection of mercury ions are provided. We believe these examples provide sufficient evidence for the potential use and progress of electrospun nanofibers toward colorimetric sensing of mercury ions. Furthermore, the summary of the review is focused on providing an insight into the future directions of designing electrospun nanofiber-based, metal ion colorimetric sensors for practical applications.